Acute Psychotic Episode Induced by Antimicrobial Treatment - Savera I. Arain; Majed Al Shakhori; Shabeer A. Thorakkattil; Omer Amin (Case Reports in Psychiatry)
Psychosis is an abnormal state of mind that leads to losing touch with reality. Symptoms may include delusions and hallucinations, amongst other features. Psychosis is known to increase the risk of other health conditions and may have serious adverse outcomes. This is a case report of a 26-year-old woman with no previous psychiatric history who presented with symptoms and signs suggestive of acute psychosis shortly after starting a postprocedural combination of antimicrobials. The patient’s family decided to stop the antimicrobials as they observed an escalation of the psychotic symptoms with the ongoing use of antibiotics. The patient was subsequently brought to the emergency service (EMS) department, and she was admitted to the behavioral health unit. The treatment team managed to stabilize the patient with several interventions, including the administration of antianxiety and antipsychotic medications along with psychosocial intervention. The symptoms of psychosis resolved within 3-4 days, and she was discharged home. Even though transient psychotic episodes have been reported previously with antibiotics, this case emphasizes the increased need for vigilance and reporting in patients receiving antimicrobials.